Dismantling America : and other controversial essays - Sowell, Thomas, 1930- (Basic Books, 2010)
These wide-ranging essays, on many individual political, economic, cultural and legal issues, have as a recurring underlying theme the decline of values and of the institutions that have sustained and advanced American society for more than two centuries. Originally published as syndicated newspaper columns, these essays are about financial bailouts, illegal immigrants, gay marriage, national security, the Duke University rape case, and other topics where the underlying concern is about what these very different topics say about the general direction of American society.